Six usable privacy heuristics - Salgado, André de Lima; Hung, Patrick C. K.; Fortes, Renata P. M. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
Enhancing privacy policy interfaces is crucial for improving users' trust in technology and ensuring compliance with legislation. This thesis focused on developing usable interfaces that enable laypeople to protect their online privacy. Through a comprehensive analysis, including literature review, thematic and cluster analysis, and empirical evaluation, six usable privacy heuristics (push#) are established. These heuristics effectively identify catastrophic problems in privacy policy interfaces for laypeople. Additionally, preliminary usable privacy guidelines (pug#) are created, and a new process for developing usability criteria is proposed. Future research directions are suggested, including the application of these heuristics and guidelines to domains like human-robot interaction and human-artificial intelligence interaction.